Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, K; Fiedler, C; Guenther, F; Grouzmann, E; Neuhuber, W; Fischer, M; Ott, C; Linz, P; Freisinger, W; Heinlein, S; Schmidt, S; Schmieder, R; et al. (American Physiological Society, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.